Meningkatkan Potensi Lokal: Pemberdayaan Perempuan Melalui Pelatihan Sulaman Kapalo Samek di Nagari Simpuruik, Tanah Datar - Alfisha Putri; Alisa Sani Mardia; Belinda Yulianti; Yulia Hanoselina; Rahmadhona Fitri Helmi (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the implementation of kapalo samek embroidery training in Nagari Simpuruik as an effort to promote economic empowerment and preserve local culture. Based on interviews with village officials and women participating in the training, it was found that most participants had already acquired embroidery skills through self-taught methods prior to the training. They were accustomed to working on embroidery either based on custom orders or in cooperation with